Daniel Bell’s Theory of the Coming of the Post-Industrial Society - Stojić, Gordana V. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
Twenty-five years after the publication of the famous Daniel Bell’s book The Coming of Post-industrial Society, new edition of the book was published with a foreword written by the author named “The Axial Age of Technology”. In the forеword Bell clarifies his theses and predictions in relation to the changes that have taken place in meantime in contemporary society, as well as regarding to the critics of his theory. The aim of the paper is to show how Bell explains social development in the second half of the twentieth century as well as the main characteristics of that society of “transitory nature” in which we live. Bell’s starting theoretical and methodological point of view are discussed as well as the explanation of transition from industrial to post-industrial society and the possibilities of development of the third world societies. The main characteristic of post-industrial society, according to Bell, is the codification of theoretical knowledge and the new relation between science and technology. Main post-industrial developments are: the rise of service sector, occupational changes, changes in professions and education, growing role of financial and human capital, new forms of infrastructure and knowledge theory of value. New form of society is emerging, with changes in stratification system, economy, organization and consumption. Bell doesn’t plead for a holistic view of society. Instead, he considers society as comprising three realms that can change in different ways, so historical change is not unified. Major instrument of historical change is technology, it poses problems for culture and political system but it doesn’t determine them. He rejects the accusations of technological determinism because technology often operates in context it doesn’t make. Daniel Bell was one of the first authors who stated that modern society had been fundamentally changing. His aim was to make a conceptual framework for the comprehensive explanation of contemporary social change. One can point to several theoretical and methodological problems Bell’s explanation of modern society faces with (as well as some other theories of social change) such as technological determinism, unilinear concept of development and so, but he has built a sociological theory of contemporary social change, which encouraged intense debate in the social sciences and set up one of the possible starting points for understanding the contemporary social dynamics, theories of the information society.